Resilient House Evaluation Matrix: Attributes and Quality Indicators for Social Housing - Simone Barbosa Villa; Karen Carrer Ruman de Bortoli; Lamonise Vasconcelos Oliveira (Buildings)
Background: This study explores resilience in Brazilian social housing (SH), focusing on single-family, one-story housing units within the “Minha Casa, Minha Vida” (MCMV) program. Despite reducing the housing deficit by delivering 7.7 million units since 2009, the program’s projects often lack resilience, contributing to social, physical, and environmental vulnerabilities. Resilience is defined as the built environment’s ability to respond, absorb, and adapt to impacts and demands, addressing vulnerability and adaptive capacity. Methods: This study developed the Resilient House Evaluation Matrix (RHEM), piloted in two MCMV developments in Uberlândia, MG, Brazil. Data were collected using performance and post-occupancy evaluation tools, focusing on attributes such as thermal comfort, energy efficiency, flexibility, and accessibility for the elderly. Indicators and sub-indicators were defined to measure resilience. Results: The RHEM attributes proved useful in improving housing quality and resilience, while evaluation tools identified key impacts and residents’ perceptions. The Resilience Ruler (RR) assessed resilience levels, supporting the development of design strategies to enhance resilience in SH. These findings align with Sustainable Development Goal (SDG) 11, contributing to resilient communities. Conclusions: This study emphasizes the importance of resilient SH design to address vulnerabilities and enhance adaptability. The RHEM provides a valuable framework for advancing housing resilience.